Critical Analysis of Healthcare Systems, Leadership Challenges, and Public Health Solutions - Majrashi, Salwa Mohammed Ali; Alqahtani, Ahlam Mshabab Saad; Alqhtani, Ashwag Mshabab Saad; Majrashi, Amjad Mohammed Ali; Alsallum, Mazen Mohammed Salem; Al dwais, Mohammed Abdulqawi; Alhasinah, Abdullah Mohammed; Alzhrani, Ali Sudan; Al zayadi, Khalid Salim; Almarhoon, Zahra Ali (Journal of Ecohumanism, 2024)
In this paper, the article provided a critique of various global health systems as well as prospects of the leadership and the general transformation of the conventional public health approaches in handling health disparities and enhancing patient care provision. Healthcare systems are built over time depending on the socio-economic factors, technology, and politics of the different regions. This paper discusses the issues that managers of healthcare organizations experience, particularly in moments of crisis— for example, epidemic or pandemic situations or resource scarcity. Also, different approaches such as universal health coverage (UHC), technology-enhanced health promotion, etc., are well discussed to examine their suitability in solving emerging challenges to world health.